The sympathetic adrenomedullary system, but not the hypothalamic-pituitary-adrenal axis, participates in aorta adaptive response to stress: nitric oxide involvement - Navarro-Oliveira, C. M.; Vassilieff, V. S.; Cordellini, S. (Elsevier B.V., 2000)
Stress induced a decrease in the reactivity of the aorta to noradrenaline (NA), as a consequence of an endothelial nitric oxide (NO) system hyperactivity. The main characteristic of the stress response is activation of the hypothalamic-pituitary-adrenal (HPA) axis and sympathetic adrenomedullary (SA) system. The participation of the HPA axis and SA system in the decreased reactivity to NA in the aorta of rats exposed to 4-h immobilization was investigated. Concentration-response relationships for NA were obtained in the aorta, with and without endothelium, isolated from normal and stressed rats, following these procedures: (1) in the absence and presence of L-NAME; (2) after adrenalectomy (ADX) or not, in the absence or presence of L-NAME; (3) ADX rats treated or not with corticosterone; (4) ADX associated with stress; and (5) treated or not with reserpine. The reactivity of aorta without endothelium was unaffected by the procedures. The reactivity of aorta with endothelium was decreased by either stress or ADX. This effect was reversed by both L-NAME and corticosterone. ADX did not potentiate the decrease in the aorta reactivity induced by stress. Reserpine did not change the reactivity of aorta with endothelium from normal rats, but prevented the decrease in reactivity induced by stress. It is concluded that the HPA axis participates in endothelium-dependent modulation of aorta reactivity in normal conditions and that thr SA system participates in hyperactivity of the endothelial NO-system induced by stress, which is responsible for the decreased aorta reactivity to NA. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: sympathetic adrenomedullary system; hypothalamic-pituitary-adrenal axis; stress; reactivity of rat aorta; endothelium; nitric oxide